V-ATPase-Mediated Granular Acidification Is Regulated by the V-ATPase Accessory Subunit Ac45 in POMC-Producing Cells - Jansen, Eric J. R. (The American Society for Cell Biology, 2010)
The vacuolar (H(+))-ATPase (V-ATPase) is an important proton pump, and multiple critical cell-biological processes depend on the proton gradient provided by the pump. Yet, the mechanism underlying the control of the V-ATPase is still elusive but has been hypothesized to involve an accessory subunit of the pump. Here we studied as a candidate V-ATPase regulator the neuroendocrine V-ATPase accessory subunit Ac45. We transgenically manipulated the expression levels of the Ac45 protein specifically in Xenopus intermediate pituitary melanotrope cells and analyzed in detail the functioning of the transgenic cells. We found in the transgenic melanotrope cells the following: i) significantly increased granular acidification; ii) reduced sensitivity for a V-ATPase-specific inhibitor; iii) enhanced early processing of proopiomelanocortin (POMC) by prohormone convertase PC1; iv) reduced, neutral pH–dependent cleavage of the PC2 chaperone 7B2; v) reduced 7B2-proPC2 dissociation and consequently reduced proPC2 maturation; vi) decreased levels of mature PC2 and consequently reduced late POMC processing. Together, our results show that the V-ATPase accessory subunit Ac45 represents the first regulator of the proton pump and controls V-ATPase-mediated granular acidification that is necessary for efficient prohormone processing.